2019
DOI: 10.3847/1538-4357/ab12df
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Simulations of Massive Stars. I. Wave Generation and Propagation

Abstract: We present the first three-dimensional (3D), hydrodynamic simulations of the core convection zone (CZ) and extended radiative zone spanning from 1% to 90% of the stellar radius of an intermediate mass (3 M ) star. This allows us to selfconsistently follow the generation of internal gravity waves (IGWs) at the convective boundary and their propagation to the surface. We find that convection in the core is dominated by plumes. The frequency spectrum in the CZ and that of IGW generation is a double power law as s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
100
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 59 publications
13
100
1
Order By: Relevance
“…However there were few firm detections of IGWs in massive stars before this study 15,16,21 . Recent two-dimensional (2D) and 3D spherical numerical simulations using a realistic stellar structure model predict the excitation of IGWs by turbulent core convection, and an amplitude spectrum for IGWs with a value between 0.8 and 3 for the frequency exponent gamma [26][27][28] . On the other hand, 3D simulations in a Cartesian box in idealized conditions predict a steeper IGW amplitude spectrum with 3.25 as the frequency exponent 30 As a next step, spectroscopy of these stars will allow the determination of fundamental stellar parameters, which are necessary to perform asteroseismic modelling and to constrain interior properties, including the measurement of a star's age, core mass and interior rotation profile.…”
Section: Discussionmentioning
confidence: 99%
“…However there were few firm detections of IGWs in massive stars before this study 15,16,21 . Recent two-dimensional (2D) and 3D spherical numerical simulations using a realistic stellar structure model predict the excitation of IGWs by turbulent core convection, and an amplitude spectrum for IGWs with a value between 0.8 and 3 for the frequency exponent gamma [26][27][28] . On the other hand, 3D simulations in a Cartesian box in idealized conditions predict a steeper IGW amplitude spectrum with 3.25 as the frequency exponent 30 As a next step, spectroscopy of these stars will allow the determination of fundamental stellar parameters, which are necessary to perform asteroseismic modelling and to constrain interior properties, including the measurement of a star's age, core mass and interior rotation profile.…”
Section: Discussionmentioning
confidence: 99%
“…Cristini et al 2017;Jones et al 2017), which affects the chemical composition profile that is left behind of the retreating hydrogen core. Furthermore, 3D simulations clearly show that at the interface of the convective and radiative region internal gravity waves are generated, that propagate to the surface (Cristini et al 2017;Edelmann et al 2019). How much these waves mix the composition needs to be determined but they definitely affect the radiative region above the convective core.…”
Section: Discussionmentioning
confidence: 99%
“…A recent discovery made using the CoRoT, K2, and TESS missions was that the vast majority of early-type stars have significant low-frequency variability in photometry (Bowman et al, 2019a,b). Such stochastic variability is not predicted from the κ-mechanism, but is expected from convectively-driven internal gravity waves (IGWs) excited by core convection (Rogers et al, 2013;Rogers, 2015;Edelmann et al, 2019;Horst et al, 2020). 2D and 3D hydrodynamical simulations predict that IGWs reach the surface with significant amplitudes and provide detectable perturbations in temperature and velocity (Edelmann et al, 2019), and that IGWs are also extremely efficient at transporting angular momentum and chemical elements (Rogers, 2015;Rogers and McElwaine, 2017).…”
Section: Diverse Photometric Variability In Massive Starsmentioning
confidence: 99%
“…2D and 3D hydrodynamical simulations predict that IGWs reach the surface with significant amplitudes and provide detectable perturbations in temperature and velocity (Edelmann et al, 2019), and that IGWs are also extremely efficient at transporting angular momentum and chemical elements (Rogers, 2015;Rogers and McElwaine, 2017). A snapshot of a 3D simulation of IGWs propagating within a 3-M ⊙ main-sequence star from Edelmann et al (2019) is shown in Figure 6.…”
Section: Diverse Photometric Variability In Massive Starsmentioning
confidence: 99%
See 1 more Smart Citation